Grandiflodines A and B, two novel diterpenoid alkaloids from Delphinium grandiflorum. Issue 39 (3rd May 2017) - Chen, Neng-Hua; Zhang, Yu-Bo; Li, Wen; Li, Pan; Chen, Li-Feng; Li, Yao-Lan; Li, Guo-Qiang; Wang, Guo-Cai
Abstract : Two novel diterpenoid alkaloids, grandiflodines A and B (1 and2 ), were isolated from Delphinium grandiflorum . Abstract : Two novel diterpenoid alkaloids, grandiflodines A and B (1 and2 ), were isolated from Delphinium grandiflorum . Compound1 represents a rare hetisine-type C20 -diterpenoid alkaloid in which the bond between the atoms of N and C-17 is broken. Compound2 features an unusual lycoctonine-type C19 -diterpenoid alkaloid skeleton with the cleavage of N–C19 and C7 –C17 bonds, and the construction of the N–C7 bond. Structural elucidations of the isolates were performed by spectroscopic analysis, X-ray diffraction and comparison with the literature. These compounds were tested for their antiviral and anti-inflammatory activities.